NURSING CARE OF ACUTE PAIN IN CLIENTS WITH ACUTE MYOCARDIAL INFARCTION IN THE ICCU ROOM, DR. SOEGIRI HOSPITALS LAMONGAN - In, Qurorin (Journal of Vocational Nursing, 2022)
Introduction: Severe pain in the center of the chest is found in acute myocardial infarction (AMI) clients. Chest pain is described as pressing, usually radiating to the jaw or teeth, shoulders, arms, and/or back. Purpose: to report a case study on nursing care of clients with acute pain in AMI clients in the ICCU Room of Dr. Soegiri Hospitals Lamongan. Methods: research using case studies. The sample used was one IMA client with acute pain. Data collection was obtained through interviews, observations, physical examinations and documentation studies. Result: the case shows that there are several gaps between the client's facts and the literature review. For the assessment of AMI clients in general there is no gap, nursing diagnoses lead to a priority, namely acute pain, with priority nursing actions taken, namely providing analgesic therapy and advising clients to perform distraction and relaxation techniques. Evaluation of the nursing diagnosis of acute pain, the problem was partially resolved on the third day. Conclusion: AMI clients in their care must be more careful in assessing and prioritizing patient needs, seriousness in implementation to avoid complications that may occur.